Prioritization of risk groups for influenza vaccination in resource limited settings – A case study from South Africa. Issue 1 (3rd January 2019) - McMorrow, Meredith L.; Tempia, Stefano; Walaza, Sibongile; Treurnicht, Florette K.; Ramkrishna, Wayne; Azziz-Baumgartner, Eduardo; Madhi, Shabir A.; Cohen, Cheryl
Highlights: Low- and middle-income countries may have limited resources for influenza vaccines. Pregnant women had the highest estimated hospitalizations averted per 100, 000 vaccinated. Persons with tuberculosis disease had lowest cost per year of life saved. Influenza vaccines prevented 247 (95% CI 99-431) deaths in South Africa in 2016. Abstract: Background: Due to competing health priorities, low- and middle-income countries (LMIC) may need to prioritize between different influenza vaccine risk groups. Risk group prioritization may differ in LMIC based upon programmatic feasibility, country-specific prevalence of risk conditions and influenza-associated morbidity and mortality. Methods: In South Africa, we collected local disease burden data (both published and unpublished) and published vaccine efficacy data in risk groups and healthy adults. We used these data to aid policy makers with risk group prioritization for influenza vaccination. We used the following formula to assess potential vaccine averted disease in each risk group: rate of influenza-associated hospitalization (or death) per 100, 000 population * influenza vaccine efficacy (VE). We further estimated the cost per hospital day averted and the cost per year of life saved by influenza vaccination. Results: Pregnant women, HIV-infected adults, and adults and children with tuberculosis disease had among the highest estimates of hospitalizations averted per 100, 000 vaccinated and adults aged 65 years and older had the highest estimated deaths averted per 100, 000 vaccinated. However, when assessing both the cost per hospital day averted (range: USD148-1, 344) and the cost per year of life saved (range: USD112-1, 230); adults and children with TB disease, HIV-infected adults and pregnant women had the lowest cost per outcome averted. Discussion: An assessment of the potential disease outcomes averted and associated costs may aid policymakers in risk group prioritization for influenza vaccination.